Novel Factors of Viral Origin Inhibit TOR Pathway Gene Expression - Salvia, Rosanna; Nardiello, Marisa; Scieuzo, Carmen; Scala, Andrea; Bufo, Sabino A.; Rao, Asha; Vogel, Heiko; Falabella, Patrizia (Frontiers in Physiology, 2018)
Polydnaviruses (PDVs) are obligate symbionts of endoparasitoid wasps, which exclusively attack the larval stages of their lepidopteran hosts. The Polydnavirus is injected by the parasitoid female during oviposition to selectively infect host tissues by the expression of viral genes without undergoing replication. Toxoneuron nigriceps bracovirus (TnBV) is associated with Toxoneuron nigriceps (Hymenoptera: Braconidae) wasp, an endoparasitoid of the tobacco budworm larval stages, Heliothis virescens (Lepidoptera: Noctuidae). Previous studies showed that TnBV is responsible for alterations in host physiology. The arrest of ecdysteroidogenesis is the main alteration which occurs in last (fifth) instar larvae and, as a consequence, prevents pupation. TnBV induces the functional inactivation of H. virescens prothoracic glands (PGs), resulting in decreased protein synthesis and phosphorylation. Previous work showed the involvement of the PI3K/Akt/TOR pathway in H. virescens PG ecdysteroidogenesis. Here, we demonstrate that this cellular signaling is one of the targets of TnBV infection. Western blot analysis and enzyme immunoassay (EIA) showed that parasitism inhibits ecdysteroidogenesis and the phosphorylation of the two targets of TOR (4E-BP and S6K), despite the stimulation of PTTH contained in the brain extract. Using a transcriptomic approach, we identified viral genes selectively expressed in last instar H. virescens PGs, 48 h after parasitization, and evaluated expression levels of PI3K/Akt/TOR pathway genes in these tissues. The relative expression of selected genes belonging to the TOR pathway (tor, 4e-bp, and s6k) in PGs of parasitized larvae was further confirmed by qRT-PCR. The down-regulation of these genes in PGs of parasitized larvae supports the hypothesis of TnBV involvement in blocking ecdysteroidogenesis, through alterations of the PI3K/Akt/TOR pathway at the transcriptional level.